2007
DOI: 10.1167/iovs.07-0048
|View full text |Cite
|
Sign up to set email alerts
|

Variable Involvement of the Perivascular Retinal Tissue in Carbonic Anhydrase Inhibitor–Induced Relaxation of Porcine Retinal Arterioles In Vitro

Abstract: A further elucidation of the mechanisms of action of carbonic anhydrase-induced dilation of retinal arterioles may contribute to a better understanding of the regulation of retinal blood flow. The perivascular retinal tissue may play a significant role in diameter control of retinal arterioles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…The experiments of the present study extend previous studies using the wire myograph to investigate the tone regulation of retinal arterioles. 6,14,15 Adenosine was shown to induce vasorelaxation that was independent of the presence of perivascular tissue, indicating a direct effect on the arteriolar wall. In previous studies it has been shown that 8-PSPT can reduce this relaxing effect 6 and that the vasodilating effect of adenosine on isolated porcine retinal arterioles is mediated by A 2A receptors but not by A 1 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…The experiments of the present study extend previous studies using the wire myograph to investigate the tone regulation of retinal arterioles. 6,14,15 Adenosine was shown to induce vasorelaxation that was independent of the presence of perivascular tissue, indicating a direct effect on the arteriolar wall. In previous studies it has been shown that 8-PSPT can reduce this relaxing effect 6 and that the vasodilating effect of adenosine on isolated porcine retinal arterioles is mediated by A 2A receptors but not by A 1 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…The vasorelaxing effect of dorzolamide was signifi cantly reduced in isolated arterioles, as evidenced by both a reduction in the maximum relaxation and an increase in EC 50 . 42 It is therefore highly likely that the vasorelaxing effect of these drugs depends on carbonic anhydrases in the perivascular tissue. This effect may have involved different membrane-bound isoenzyme IV and XIV located in retinal astrocytes and Müller cells.…”
Section: Discussionmentioning
confidence: 99%
“…The diffusion distance from the point of drug application (the cornea) to the ciliary body is much shorter than the distance to the posterior choroid measurement site, and so greater drug delivery may explain the more robust ciliary response. However, dorzolamide’s vascular mechanism of action is presumed to be caused by tissue hypercapnia or changes in local pH, 21,22,46 and the greater amount of metabolically active tissue adjacent to the resistance arterioles in the ciliary body than in the choroid may also contribute to the discrepant vascular effects.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 In vitro studies also show a direct vasodilatory effect of CAIs on retinal arterioles. 21,22 Given the ambiguity in the reported ocular blood flow responses to dorzolamide, one goal of the present study was to determine its effects on choroidal and ciliary blood flow at different perfusion pressures in an established rabbit model, 23,24 which had not been done previously.…”
mentioning
confidence: 99%